Dynamic Behavior of Connected Structures - Kamarudin, Ahmad Fahmy; Mokhatar, Shahrul Niza; Seyed Hakim, Seyed Jamalaldin; Ibrahim, Zainah; Ibrahim, Azmi; Faisal, Ade (International Journal of Integrated Engineering, 2022)
The effect of connected structure on SMK Bukit Tinggi building was investigated based on their dynamic behaviour. The structure was constructed with four main buildings are interconnected. Ambient vibration testing (AVT) was used to predict the dynamic response and characteristics by using triaxial 1Hz seismometer and CityShark data logger. The AVT signals were analysed using GEOPSY software for Fourier Amplitude Spectral (FAS). All predominant frequencies (fo) and mode shapes were identified and verified with previous research finding using similar testing approach on the same building, but with different instrument of accelerometer sensor and ARTeMIS software processing tool. Five modes of fo were found from the FAS curves from this research, but only four fo were obtained from ARTeMIS analysis. The highest deviation percentage was indicated at the 5th mode of building frequency at 9.5 %, but 0 to 2.5% to the rest frequencies mode (1st to 4th frequencies mode). Ununiformed buildings response behaviour was believed to contribute, and initiate active progressive shear cracking on the slab panels, columns, beam and at the reentrant corners between laboratory and academic buildings of Building C. It worst when the buildings were struck by several earthquakes’ series. The unsynchronised oscillation between adjacent buildings to Building C had induced couple lateral and torsional deformations. The structural and non-structural damages mostly concentrated at the reentrant corners and mid-span of the building, which identical to the location of maximum deflection amplitudes. In conclusion, strict attention must be emphasized on the fo and mode shapes based on their dynamic response and characteristics analyses, which could be altered by the presence of connected structures.